If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-3x + -5) = -4x Reorder the terms: -2(-5 + -3x) = -4x (-5 * -2 + -3x * -2) = -4x (10 + 6x) = -4x Solving 10 + 6x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 10 + 6x + 4x = -4x + 4x Combine like terms: 6x + 4x = 10x 10 + 10x = -4x + 4x Combine like terms: -4x + 4x = 0 10 + 10x = 0 Add '-10' to each side of the equation. 10 + -10 + 10x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 10x = 0 + -10 10x = 0 + -10 Combine like terms: 0 + -10 = -10 10x = -10 Divide each side by '10'. x = -1 Simplifying x = -1
| (x^3+x^2+x+1)*(11x-7)= | | 9+y+5=30 | | 10=15(x-4) | | K/9=-3 | | 7z=4z+3 | | 12=(N+4) | | -2(6+5n)=28-2n | | 4x+12=2(x+12) | | 15=a-326 | | 10=7(n+5) | | 4/3*(6y) | | 13+g=15 | | 3(2x+5)+3=60 | | 5h+10=15 | | t-12=26 | | 5+6s=2s-7 | | 2(4n+3.2)=46.4 | | 4y+3x=55 | | 2(4n+3.2)=46.2 | | 1.5d+3.25=1+2.25x | | x^2+10x=c | | -2.4p=14.4 | | 7x-4+x=1 | | 3.4*(-2)=x-(-4) | | -5w=-6w+7 | | Y+5.4=-7.8 | | 12(4c-9)=4c-5 | | 19-12+6r-2r=18 | | x^2+16x=-50 | | -70+6x+2x=34 | | -x+7x-7+2=2x+2 | | 9x-179+2x=96 |